PERENCANAAN KAPASITAS AIR SIDE BANDAR UDARA WIRIADINATA KOTA TASIKMALAYA - Alviany Sunendar, Syifa; saepudin, Uu Saepudin; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2025)
Wiriadinata Airport, Tasikmalaya City was only opened in 2017. Considering the increasing number of passengers at Wiriadinata Airport, Tasikmalaya City, which is increasingly growing. Discusses plans for developing airside facilities at Wiriadinata Airport, Tasikmalaya City, that are needed to serve additional airport users for the next 10 years based on the runway, taxiway and apron capacity requirements of Wiriadinata Airport in current conditions. This research uses the planned Boeing 737 MAX 8 aircraft by calculating passenger arrival patterns, namely predicting estimated passenger capacity in the past 5 years as well as analyzing passenger capacity or supply and demand in 2034. Forecasting calculation method by carrying out analysis to determine aircraft movements in 2034, by comparing data on aircraft annual flight, a linear regression analysis model is used to determine the number of aircraft movements in 2034. From the discussion of air side capacity planning for Wiriadinata Airport, Tasikmalaya City The capacity of this airside facility is that the number of aircraft movements in 2024 will be 6 flights a day, in 2028 there will be 8 flights and in 2034 there will be 10 flights a day at Wiriadinata Tasikmalaya airport with the assumption of a departure to flight ratio of 50%. The runway capacity in 2024 is 27 flights per year and the apron area is 11,450.18 m², the runway capacity in 2024 is 23 flights and the apron area is 11,450.18 m², while in 2034 the runway capacity is 23 and the apron area is 13,021.28 m². The taxiway capacity based on the taxiway capacity calculation analysis is 60 movements so no additional taxiway is needed. Alternative control can be done by improving facilities on the runway and apron side to support airport operations